Influence of carbacetam on neurologic destruction processes under the experimental traumatic brain injury - Ziablitsev, S. V.; Starodubska, O. O.; Diadyk, O. O. (Journal of Education, Health and Sport, 2017)
Objective of the research. Provide the research of the influence of Carbacetam on the neurologic destruction processes in paraventricular and supraoptic nuclei of the hypothalamus under the experimental traumatic brain injury (TBI). Materials and methods of the research. The research was held by means of white outbred male rats weighing 200±10 g. The modulation of the traumatic brain injury was based on the method of V.M. Eslki and S.V. Ziablitsev (2008), where the TBI was caused due to gravity load on animals with the strike energy of 0.52 J. The lethal outcome during the first 5 days after the TBI was 84%. The control group (n=10) was administered 1 ml of saline intraperitoneally within the 10 days after TBI. The rats of experimental group (n=10) were provided Carbacetam (5 mg per 1 kg) in 1 ml of saline. After the experiment, the animals were decapitated followed by the removal of the brain, and the histological medicines were produced by means of Microtome after the appropriate histological processing. Some sections were stained with hematoxylin and eosin, others - properly prepared before applying the neuromarkers NSE, S-100 and GFAP. The morphological and immune histochemical evaluation of neurodegenerative changes in the nerve tissue were done by the produced medicines. Outcomes and discussion of them. The outcomes of the research show that Carbacetam influences the decrease of the degenerative processes in the neural tissue of paraventricular and supraoptic nuclei of the hypothalamus. The neurons of the animals after TBI being administered with the Carbacetam, are characterized by the restoration of the normal morphological features unlike the rats that did not receive the medicine. Immune histochemical research of the brain neuronal markers confirms the functional recovery of the neurons and astrocytes in the researched areas of the hypothalamus of the rats after administration of Carbacetam. The decrease in the expression of glial markers GFAP and S-100 has been observed, showing the reduction of degenerative changes in the neural tissue. Meanwhile, the expression of neuronal marker NSE has increased, showing high metabolic activity of the nerve cells. However, changes in the expression of the neural markers and glia feature the restoring of normal neuronal activity due to the administration of Carbacetam. Therefore, further research of Carbacetam effects is promising in terms of restoring the neuronal destruction under TBI.